PENGARUH PENGUNGKAPAN CSR, LABA AKUNTANSI, DAN ARUS KAS TERHADAP ABNORMAL RETURN PADA PERUSAHAAN MANUFAKTUR YANG TERDAFTAR DI BURSA EFEK INDONESIA (BEI) TAHUN 2014-2017 - Vivi Nur Malasari, 14.05.52.0248; Indarti, MG. Kentris (Students' Journal of Accounting and Banking, 2019)
The purpose of this research was to analyze the effect of CSR Disclosures, Accounting Profits, Operating Cash Flows, Investment Cash Flow, and Funding Cash Flow on Abnormal Return. The population in this study are all manufacturing companies listed on the Indonesia Stock Exchange in 2014-2017. The data analysis tool used in this study is descriptive analysis and multiple regression analysis. The results of this study indicate that CSR disclosure has a negative effect not significantly on Abnormal Return. Accounting Profit has a negative effect not significant on Abnormal Return. Operating Cash Flow has a positive and insignificant effect on Abnormal Return. Investment Cash Flow negative effect is not significant on Abnormal Return. Funding Cash Flow has a significant negative effect on Abnormal Return.